Jemaat Lanjut Usia yang Berbahagia: Pelayanan, Pembinaan, dan Pendewasaan Iman - Sarah Silalahi; Segen Pasaribu; Angelina Pasaribu; Ramayanti Pangaribuan; Maria Widiastuti (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2022)
Older people tend to stay at home, a condition that poses new problems for older people. They are alienated from their environment and forgotten by people, resulting in rejection and loss of self-esteem. Therefore, church ministry to the elderly must be viewed as a specific ministry and taken seriously by special workers and servants of God who truly understand the problems of the elderly. These categorical services morally oblige the church to treat its congregation members, the elderly, seriously and responsibly. Ultimately it means striking a balance between being careful and acting responsibly. A church is an institution with an organization. But more than that, the church is a community of believers. According to God's command in Matthew 28: 18-20, After becoming a disciple of Christ and being baptized, a disciple of Christ must be taught the doctrine of the Christian faith, how to live the Christian life.